2017
DOI: 10.1038/srep46579
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differentiation of five Cinnamomum camphora chemotypes using desorption atmospheric pressure chemical ionization mass spectrometry of raw leaves

Abstract: Five chemotypes, the isoborneol-type, camphora-type, cineole-type, linalool-type and borneol-type of Cinnamomum camphora (L.) Presl have been identified at the molecular level based on the multivariate analysis of mass spectral fingerprints recorded from a total of 750 raw leaf samples (i.e., 150 leaves equally collected for each chemotype) using desorption atmospheric pressure chemical ionization mass spectrometry (DAPCI-MS). Both volatile and semi-volatile metabolites of the fresh leaves of C. camphora were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…It is a common phenomenon that noteworthy differences in chemical composition exist between individuals of the same species in the genus Cinnamomum (Guo et al, 2017;Singh et al, 2012;Teles et al, 2019). For example, there are at least five chemotypes in C. camphora, including the borneol type, linalool type, camphor type, nerolidol type and 1,8-cineole type (Chen et al, 2018).…”
Section: Validation Of Degs Using Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…It is a common phenomenon that noteworthy differences in chemical composition exist between individuals of the same species in the genus Cinnamomum (Guo et al, 2017;Singh et al, 2012;Teles et al, 2019). For example, there are at least five chemotypes in C. camphora, including the borneol type, linalool type, camphor type, nerolidol type and 1,8-cineole type (Chen et al, 2018).…”
Section: Validation Of Degs Using Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…There is chemical polymorphism in C. camphora . According to the signature constituent in leaf, C. camphora was classified into at least five different chemical variants (chemotypes), including linalool- (58–92%), borneol- (67–82%), camphor- (54–97%), cineole- (32–52%), and nerolidol-types (16–57%) [ 4 , 5 ]. In recent years, C. camphora has become of increasing importance as a source of essential oils, especially for the production of natural borneol and linalool [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Borneol is a cyclic monoterpene alcohol extracted from Cinnamomum camphora (L.) and other plants [ 54 ]. Silva-Filho et al [ 55 ] demonstrated that borneol promoted the relaxation of aortic rings that were pre-contracted with phenylephrine or KCl − in a concentration-dependent and endothelium-independent manner.…”
Section: Resultsmentioning
confidence: 99%